On the relationship between residential property rental values and infrastructure provision in Abaji City F.C.T, Nigeria / Abass Iyanda Sule - Sule, Abass Iyanda (Faculty of Architecture, Planning & Surveying and UiTM Press, 2013)
Property value is dependent upon many features related with that property such as physical features of the property: location in relation to accessibility and other neighbourhood infrastructure does affect value. Those attributes are usually provided by the State in the case of a State and Local governments through their various policies and services. This study focuses on the relationship between residential property rental value and the available infrastructural facilities in residential properties in Abaji, F.C.T Nigeria and analysed their influence in the determination of the rental values of the properties. Data for this work were collected through structured questionnaire and administered based on stratified random sampling (i.e. zones of traditional and non-traditional residences). Data collected for the assessment include, house structural characteristics, inhouse and environmental facilities. Analysis of data was done by factor analysis with statistical package for social science (SPSS 10.0) and excel package. The results depict that; compound houses and bungalows dominate Abaji City which together contributed about 66.1% of the total stock of houses. The study revealed that, there is positive relationship between the type of building and rental value, 36.4% variations in annual rental are predicted by building types and 28.4% variations in annual rent are predicted by the accessibility to houses in Abaji City. Based on the findings, one of the recommendations made is that, building regulations must be in operation or enforced by the appropriate officers of local.